2004
DOI: 10.1038/modpathol.3800071
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of manual dissection of lymph nodes in colon cancer resections

Abstract: The adequacy of lymph node dissection of colonic resection specimens influences the clinical and pathologic staging, leading to important postsurgical treatment decisions. Although manual lymph node dissection is the current standard at most institutions, recent statistical studies indicate that all lymph nodes, including those measuring 1-2 mm, should be recovered to be assured of lymph node negative status. Thus, we tested the efficacy of gross dissection by submitting the entire residual mesenteric fat. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 23 publications
(13 reference statements)
3
70
0
1
Order By: Relevance
“…Only 2 out of 305 affected lymph nodes were that small. Similar findings were reported by Brown et al 17 Several studies showed that the number of lymph nodes investigated is of remarkable prognostic relevance mainly in stage II but also in stage III colon cancer. There are three potential factors that could influence lymph node harvest and prognosis: the surgeon, the pathologist and the patient.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Only 2 out of 305 affected lymph nodes were that small. Similar findings were reported by Brown et al 17 Several studies showed that the number of lymph nodes investigated is of remarkable prognostic relevance mainly in stage II but also in stage III colon cancer. There are three potential factors that could influence lymph node harvest and prognosis: the surgeon, the pathologist and the patient.…”
Section: Discussionsupporting
confidence: 90%
“…The metastatic involvement of lymph nodes as small as 1 mm is described in the literature. 17 However, the clinical significance of such findings is unclear. Radiologists screen their images for the occurrence of large lymph nodes (Z10 mm) in order to detect metastatic diseases.…”
mentioning
confidence: 99%
“…This seems to be even more remarkable when taking into account that the average number of collected nodes in the unstained group is 1474, which is clearly above mean values reported in the literature for conventional techniques. 6,12,22 Fat clearance methods, or complete fat embedding, produced lymph node numbers between 55 and 87 10,17,23 and showed increased identification of positive nodes. However, these techniques are time consuming and laboring.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a broad spectrum of techniques beginning with fat clearance methods to sentinel techniques has been introduced in order to increase lymph node counts and improve accuracy. [9][10][11] Nevertheless, dissection of lymph nodes in colorectal specimens is often time consuming and especially in cases of neoadjuvant radiotherapy frustrating. Increasing age, American Society of Anesthesiology grade, and preoperative radiotherapy are found to be factors for reduced lymph node harvest.…”
mentioning
confidence: 99%
“…There are advanced and resource demanding pathologic l techniques for fat clearance that would allow for the acquisition of even more lymph nodes than the standard techniques that are usually employed [32,33]. Furthermore, the numbers of lymph nodes can vary based on the location of the specimen resected as well as the body habitus and age of the patient [34][35][36].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%